Sparing nature : the conflict between human population growth and earth's biodiversity - McKee, Jeffrey Kevin (Rutgers University Press, 2003)
Annotation "Are humans too good at adapting to the earth's natural environment? Every day, there is a net gain of more than 200,000 people on the planet - that's 146 a minute. Has our explosive population growth led to the mass extinction of countless species in the earth's plant and animal communities?" "Jeffrey K. McKee contends it has. The more people there are, the more we push aside wild plants and animals. In Sparing Nature, he explores the cause-and-effect relationship between these two trends, demonstrating that nature is too sparing to accommodate both a richly diverse living world and a rapidly expanding number of people. The author probes the past to find that humans and their ancestors have had negative impacts on species biodiversity for nearly two million years, and that extinction rates have accelerated since the origins of agriculture. Today entire ecosystems are in peril due to the relentless growth of the human population."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved